Clinical effect of different doses of ciprofol for induction of general anesthesia in elderly patients: A randomized, controlled trial - Gongchen Duan; Haiyan Lan; Weifeng Shan; Yini Wu; Qiaomin Xu; Xiaoli Dong; Peiyi Mei; Minji You; Linfei Jin; Jimin Wu (Pharmacology Research & Perspectives, 2023)
Abstract Ciprofol is a newly developed intravenous anesthetic agent with improved pharmacokinetic properties. Compared to propofol, ciprofol exhibits stronger binding to the GABAA receptor and elicits a greater enhancement of GABAA receptor‐mediated neuronal currents in vitro. The aims of the present clinical trials were to examine the safety and efficacy of different doses of ciprofol for induction of general anesthesia in elderly patients. A total of 105 elderly patients undergoing elective surgery were randomized, in a 1:1:1 ratio, to receive one of three sedation regimens: (1) the C1 group (0.2 mg/kg ciprofol), (2) the C2 group (0.3 mg/kg ciprofol), (3) the C3 group (0.4 mg/kg ciprofol). The primary outcome was the incidence of various adverse events, including hypotension, hypertension, bradycardia, tachycardia, hypoxemia, and injection pain. The secondary outcomes of efficacy were the success rate of general anesthesia induction, the time to anesthesia induction, and the frequency of remedial sedation was recorded in each group. Adverse events occurred in 13 patients (37%) in group C1, 8 patients (22%) in group C2, and 24 patients (68%) in group C3. Compared with group C2, the total incidence of adverse events was significantly higher in group C1 and group C3 (p < .001).The success rate of general anesthesia induction in the three groups was 100%. Compared with group C1, the frequency of remedial sedation was significantly lower in group C2 and group C3. The outcomes demonstrated that ciprofol at a dose of 0.3 mg/kg has good safety and efficacy in the induction of general anesthesia in elderly patients. Overall, ciprofol is a new and viable option for the induction of general anesthesia in elderly patients undergoing elective surgery.